Plasmodium falciparum Merozoite Surface Proteins Polymorphisms and Treatment Outcomes among Patients with Uncomplicated Malaria in Mwanza, Tanzania. (23rd November 2022) - Marwa, Karol J.; Lyimo, Eric; Konje, Eveline T.; Kapesa, Anthony; Kamugisha, Erasmus; Swedberg, Göte
Abstract : Background . The severity of malaria infection depends on the host, parasite and environmental factors. Merozoite surface protein (msp) diversity determines transmission dynamics, P. falciparum immunity evasion, and pathogenesis or virulence. There is limited updated information on P. falciparum msp polymorphisms and their impact on artemether-lumefantrine treatment outcomes in Tanzania. Therefore, this study is aimed at examining msp genetic diversity and multiplicity of infection (MOI) among P. falciparum malaria patients. The influence of MOI on peripheral parasite clearance and adequate clinical and parasitological response (ACPR) was also assessed. Methods . Parasite DNA was extracted from dried blood spots according to the manufacture's protocol. Primary and nested PCR were performed. The PCR products for both the block 2 region of msp1 and the block 3 regions of msp2 genes and their specific allelic families were visualized on a 2.5% agarose gel. Results . The majority of the isolates, 58/102 (58.8%) for msp1 and 69/115 (60.1%) for msp2, harboured more than one parasite genotypes. For the msp1 gene, K1 was the predominant allele observed (75.64%), whereas RO33 occurred at the lowest frequency (43.6%). For the msp2 gene, the 3D7 allele was observed at a higher frequency (81.7%) than the FC27 allele (76.9%). The MOIs were 2.44 for msp1 and 2.27 for msp2 (p = 0.669 ). A significant correlation between age and multiplicity of infection (MOI) for msp1 or MOI for msp2 was not established in this study ( rho  = 0.074, p = 0.521 and rho  = −0.129, p = 0.261, respectively). Similarly, there was no positive correlation between parasite density at day 1 and MOI for both msp1 ( rho  = 0.113, p = 0.244 ) and msp2 ( rho  = 0.043, p = 0.712 ). The association between MOI and ACPR was not observed for either msp1 or mps2 (p = 0.776 and 0.296, respectively). Conclusions . This study reports high polyclonal infections, MOI and allelic frequencies for both msp1 and msp2. There was a lack of correlation between MOI and ACPR. However, a borderline significant correlation was observed between day 2 parasitaemia and MOI.